Social Peace Among Pre-Islamic Arabs (Islamic Sciences Journal, 2023)
ABSTRACT                             There is no doubt that wars, conflicts and quarrel in any country or society lead to a disruption of the security situation, which is the basis for the progress and prosperity of society, as security stability leads to the prosperity of the economic situation, which in turn is the basis for the recovery of societies. It has civilization.Before Islam, Arabs realized this fact, so they resolved that peace and security would prevail in their society, so that they could trade their goods across the desert and desert areas on the one hand, and on the other hand, so that traders could bring their goods to them, safe and secure in their lives, money, and goods. forbidden.And they chose the pilgrimage season to the Holy Kaaba of Mecca, in which the commercial markets are held, so that the far and near are safe and secure, and they would avoid war and fighting unless someone attacked them, for they would be forced to defend their protection and honor.On this basis, the Arabs before Islam were a peaceful nation, contrary to what was attached to them of the character of war and conflict, always striving to spread peace among the members of society.
Keywords: The market, Doma market, Al-Mashkar market, Sohar market, Dibba market, Al-Shahr market, Dhi Al-Majaz market.